Thyroid Hormone Is Related to Postoperative AKI in Acute Type A Aortic Dissection - Liu, Jihong; Xue, Yuan; Jiang, Wenjian; Zhang, Hongjia; Zhao, Yuanfei (Frontiers in Endocrinology, 2020)
Background: Renal function is profoundly influenced by thyroid hormone levels. This study was designed to evaluate the association between preoperative thyroid hormones and postoperative acute kidney injury (AKI) in acute type A aortic dissection (ATAAD) patients. Methods: A total of 88 patients with ATAAD who underwent surgeries in Beijing Anzhen Hospital and 274 healthy controls from July 2016 to December 2016 were included in this study. Propensity-score matching was used to compare thyroid hormone levels. Additionally, in a cohort study of ATAAD patients, multivariable regression and stratification analyses were conducted to examine the association of preoperative thyroid hormones with postoperative AKI. Results: Compared with healthy controls, ATAAD patients presented with lower preoperative levels of total triiodothyronine (TT3) (P < 0.01), free triiodothyronine (FT3) (P < 0.01), and thyroid-stimulating hormone (TSH) (P < 0.01) and a higher preoperative level of free thyroxine (FT4) (P < 0.01). The overall occurrence of postoperative AKI was 45.5%. Multivariate regression revealed that low levels of TT3 (OR = 0.07, 95% CI, 0.01-0.86, P = 0.04) was independently associated with postoperative AKI. Subgroup analyses showed that the association between TT3 and AKI was significant in patients with normal TSH levels (OR = 0.001 95% CI, 0.001-0.16, P < 0.01) but not in patients with lower TSH levels (P = 0.12). Conclusion: The present study showed that a low level of TT3 was a predictor of postoperative AKI in ATAAD patients, especially in patients with normal TSH. The thyroid function should be checked before surgical intervention of patients with ATAAD, and patients with low T3 might be at higher risk of postoperative AKI.